Evaluation of the Efficacy of Oxygen-releasing Gel as an Adjunct to Scaling and Root Planing in Chronic Periodontitis: A Split-mouth Randomized Controlled Trial - Shristi Agarwal; Shweta Bali; Priyanka Aggarwal; Amit Garg; Aruna Nautiyal; Manish Sharma (Journal of International Clinical Dental Research Organization)
Background: The aim of the study was to clinically and microbiologically evaluate the efficacy of an oxygen-releasing gel as an adjunct to scaling and root planing (SRP) in chronic periodontitis. Materials and Methods: The study was in accordance with the ethical standards of the Indian Council of Medical Research. A total of selected 30 sites were divided into Group A (control) – SRP and Group B (Test) – SRP with oxygen-releasing gel. Plaque index (PI), gingival index (GI), pocket probing depth (PPD), and clinical attachment level (CAL) were recorded at baseline, 1, and 3 months. A plaque sample was sent for microbiological analysis (culture for colony count and polymerase chain reaction [PCR]) at baseline and 3 months. All Clinical and microbiological analysis were performed, and information was fed into an Excel® database for subsequent statistical analysis (SPSS 22.0). Results: A statistically significant difference in PI, GI, PPD, and CAL in both the groups was observed between baseline, 1, and 3 months (P < 0.05). Intergroup comparison showed a statistically higher significant reduction in PPD (3.60 ± 0.507 vs. 4.93 ± 0.594) and CAL ((3.60 ± 0.507 vs. 4.93 ± 0.594) in the test group when compared to the control group at 3 months from baseline. Reduction in colony count and PCR values of Porphyromonas gingivalis between baseline and 3 months was more in the test Group 3-month follow-up. However, no statistically significant difference was found in PI and GI between both groups. Conclusion: Oxygen-releasing gel, as an adjunct to SRP, is beneficial compared to scaling and root planning alone in chronic periodontitis.